Polish LVCSR in the Janus system. Preliminary results for the SpeeCon database - Krzysztof MARASEK (Archives of Acoustics, 2014)
This paper describes the development of the LVCSR (Large Vocabulary Continuous Speech Recognition) system for Polish, using the Janus system developed at the University Karlsruhe/Carnegie Mellon University. The system has been tested on the selected material from the SpeeCon database. Test results for sentences read by 16 speakers are given. The system shows good performance and can be used as a basis for further development of modern speech recognition technology for Polish.